Journal of Pediatric Nursing: Nursing Care of Children and Families Vol.31 Issue 1, January/February 2016 Editor, Cecily Lynn Betz - Redaksi (Elsevier, 2016)
- Understanding Genetics and Pediatric Cardiac Health - In the Dark: Challenges of Caring for Sons with Klinefelter Syndrome - Parent Perceptions of Care Received by Children With an Autism Spectrum Disorder - ...